2016
DOI: 10.3847/0004-637x/825/2/90
|View full text |Cite
|
Sign up to set email alerts
|

Maps of Evolving Cloud Structures in Luhman 16ab From HST Time-Resolved Spectroscopy

Abstract: WISE J104915.57-531906.1 is the nearest brown dwarf binary to our solar system, consisting of two brown dwarfs in the L/T transition: Luhman 16A and B. In this paper, we present the first map of Luhman 16A, and maps of Luhman 16B for two epochs. Our maps were created by applying Aeolus, a Markov-Chain Monte Carlo code that maps the top-of-the-atmosphere (TOA) structure of brown dwarf and other ultracool atmospheres, to light curves of Luhman 16A and B using the Hubble Space Telescope's G141 and G102 grisms. Ae… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 31 publications
11
54
0
Order By: Relevance
“…Modeling approaches that combine multiple 1D models (such as the one presented herein and Artigau et al 2009;Apai et al 2013;Karalidi et al 2015Karalidi et al , 2016 can reproduce correlated variability or 180°anticorrelated variability, but not other phase shifts. As demonstrated above, where the "top-ofatmosphere" occurs varies depending on wavelength and the specific opacity sources that dominate at different atmospheric levels.…”
Section: Theoretical Consideration Of Observed Amplitudes and Phase Smentioning
confidence: 95%
“…Modeling approaches that combine multiple 1D models (such as the one presented herein and Artigau et al 2009;Apai et al 2013;Karalidi et al 2015Karalidi et al , 2016 can reproduce correlated variability or 180°anticorrelated variability, but not other phase shifts. As demonstrated above, where the "top-ofatmosphere" occurs varies depending on wavelength and the specific opacity sources that dominate at different atmospheric levels.…”
Section: Theoretical Consideration Of Observed Amplitudes and Phase Smentioning
confidence: 95%
“…The radiative-cloud-driven variability provides a theoretical foundation to understand the rapidly evolving light curves found for many L and T dwarfs (e.g., Artigau et al 2009;Metchev et al 2015;Apai et al 2017). These observations are difficult to explain by rotational modulation caused by temporally steady or slowly evolving surface inhomogeneity (Karalidi et al 2016), for example, phenomena analogous to the Great Red Spot or 5-µm hot spots in Jupiter's atmosphere. Light curves of many brown dwarfs can only be explained when the surface features evolve over timescales comparable to the rotation period.…”
Section: Implications For Observationsmentioning
confidence: 99%
“…The inhomogeneous brightness likely results from surface patchiness comprised of horizontally varying cloud and temperature structure (e.g., Radigan et al 2012;Apai et al 2013;Buenzli et al 2015;Karalidi et al 2016), but the mechanisms driving the surface patchiness and controlling its evolution remain elusive. Since clouds are tracers advected by atmospheric flows, and the clouds themselves result from dynamics, the patchiness also likely has a dynamical origin.…”
Section: Introductionmentioning
confidence: 99%
“…The spectra of L dwarfs (1300-2200 K; Stephens et al 2009) are best fit by models that include a thick cloud layer of iron, silicates, and corundum (Saumon & Marley 2008). Those clouds break up non-uniformly and disappear as brown dwarfs grow cooler and enter the T dwarf sequence (500-1300 K; Stephens et al 2009), as indicated by the near-infrared (IR) colors (Burgasser et al 2002), photometric and spectral variability (Buenzli et al 2014;Burgasser et al 2014;Radigan et al 2014;Wilson et al 2014;Yang et al 2016), and surface maps Karalidi et al 2016) of objects near the L/T transition. Clouds may appear again below 900 K based on the colors of late T dwarfs, this time in the form of sulfides (Morley et al 2012).…”
Section: Introductionmentioning
confidence: 99%